Lots of loss with little scrutiny: The attrition of habitat critical for threatened species in Australia. Issue 11 (8th September 2019) - Ward, Michelle S.; Simmonds, Jeremy S.; Reside, April E.; Watson, James E. M.; Rhodes, Jonathan R.; Possingham, Hugh P.; Trezise, James; Fletcher, Rachel; File, Lindsey; Taylor, Martin
Abstract: Australia has one of the worst extinction rates of any nation, yet there has been little assessment of the effect of its flagship environmental legislation, the Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act), to prevent species extinction. By coupling remotely sensed forest and woodland data with the distributions of 1, 638 terrestrial threatened species, terrestrial migratory species, and threatened ecological communities, we quantified the loss of potential habitat and communities since the EPBC Act came into force in 2000. We found that over 7.7 million ha of potential habitat and communities were cleared in the period 2000–2017. Of this clearing, over 93% was not referred to the Federal Government for assessment, meaning the loss was not scrutinized under the EPBC Act. While 1, 390 (84%) species suffered loss, Mount Cooper striped skink, Keighery's macarthuria, and Southern black‐throated finch lost 25, 23, and 10% of potential habitat, respectively. Iconic Australian species, such as koala, also lost ~1 million ha (2.3%) of potential habitat. Our analysis showed that the EPBC Act is ineffective at protecting potential habitat for terrestrial threatened species, terrestrial migratory species, or threatened ecological communities. We recommend that when scientifically determinable, critical habitat is demarcated for listed species and communities, which provides absolute protection that is enforced, monitored, and investigated by the regulator. Without a fundamental change in how environmental law is enforced, Australia faces an increasing extinction rate.